METHODS OF TRAINING OF TEACHERS OF TECHNICAL UNIVERSITY ON ADVANCED TRAINING COURSES - Shomurotova, Nigora; Ismailova, Zukhra; Nargiza , Abduvalievna (Архив научных исследований, 2021)
ABSTRACT: In this article, one of the global tasks of innovative development in the world is creativity, acmeological competence and professionalism of teachers around the world, including the creation of new ideas for creativity in people, the ability to solve complex processes, the creative approach to professional activities, the ability to take reasonable risks and professional competence. development of creativity, traditional and modern teaching methods through information and communication technologies and programs, socio-economic problems, such as intellectual resources, in order to create an appropriate role in the increase, the listed action strategy for the further development of the Republic of Uzbekistan includes the following areas: “further improvement of the lifelong education system, expanding opportunities for high-quality educational services, continuing the policy of training highly qualified specialists in accordance with modern requirements labor market. " In this regard, the importance of creativity of higher education teachers is emphasized.